ANALISIS PENGARUH ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP DAYA SAING USAHA JAM TANGAN ALBA DI SEIKO BOUTIQUE SUN PLAZA MEDAN - Iventura Fitra Uli Tamba; Mario Andrias Kiton; Fiona (Journal Publicuho, 2024)
This research aims to elucidate the simultaneous and partial effects of Market Orientation and Product Innovation on Business Competitiveness at Seiko Boutique Sun Plaza Medan. Business competitiveness significantly influences a company's ability, as well as an industry's capability, to produce goods and services, resulting in improved income and sustainable employment amidst global competition. The study employs a quantitative research approach, utilizing primary data collected through a questionnaire distributed to 97 visitors. Data processing utilizes SPSS, and the analytical tool employed is Multiple Linear Regression Analysis. The results of hypothesis testing indicate that Market Orientation has a positive and significant impact on Business Competitiveness at Seiko Boutique Sun Plaza Medan, as evidenced by the calculated tvalue (3.659) > ttable (1.985) at a significance level of 0.000 < 0.05. Similarly, the hypothesis testing results show that Product Innovation has a positive and significant influence on Business Competitiveness at Seiko Boutique Sun Plaza Medan, with a calculated tvalue (3.192) > ttable (1.985) at a significance level of 0.000 < 0.05. Simultaneously, the hypothesis testing reveals that both Market Orientation and Product Innovation have a positive and significant impact on Business Competitiveness at Seiko Boutique Sun Plaza Medan, supported by an Fvalue (40.220) > Ftable (3.093) with a significance level of 0.000 < 0.05.